Efisiensi Produksi dan Pencapaian Target di Visi Iy Nike PT. Nikomas Gemilang yang Benar Sertakan Para Ahli dan Dapusnya - Asep Munir Hidayat; Susi Resiana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Community service at the Visi Iy Nike production unit was carried out using a descriptive qualitative and participatory approach to understand real conditions and challenges in the field. The activities began with direct observation of the production process to map workflows, identify operational obstacles, and evaluate the efficiency of resources, including labor, machinery, and production time. In addition, in-depth interviews and group discussions were conducted to collect information regarding production constraints and strategies applied by the operators. The data were analyzed descriptively to identify gaps between production targets and actual outcomes. Based on these findings, several interventions were implemented, including operator skill training, assistance in production planning, and the application of simple lean manufacturing principles to reduce waste and improve efficiency. The results showed that the average production efficiency reached 77%, supported by skilled operators, adequate raw materials, and flexible management practices. Routine documentation and systematic recording of production targets also contributed to better monitoring, evaluation, and faster decision-making processes.